PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA PRODUCTORA DE BOCADILLOS DE PANELA, MANÍ Y COCO RALLADO, EN EL CANTÓN OLMEDO Y SU COMERCIALIZACIÓN EN LA CIUDAD DE LOJA - Ayala Espinoza, Martha Mercedes (2016)
The present research work was conducted with the purpose of carry out a "FEASIBILITY PROJECT FOR THE IMPLEMENTATION OF A PRODUCER COMPANY OF BOCADILLOS DE PANELA, MANÍ Y COCO RALLADO, IN OLMEDO TOWN AND THEIR MARKETING IN LOJA CITY." For this reason the aim of this idea is to give consumers a product with added value such as coco rallado, taking advantage of available resources, qualified labor, raw materials and thereby contributing to social-economic development of the Olmedo town. For the study of this research and to support this project, methods and research techniques were used, the methodology used in this research work was descriptive, because it described the capability, the characteristics of the given problem, the main functions of the research; then, the technique of survey was taken into account which was applied to the families of Loja City, with a sample of 381 surveys and another one was given to the providers of the product. In the market research, the demand and the offer were analyzed to determine the acceptance that the product has on the market. Later was analyzed the technical study where the installed and used capability were took into account as well as the size and location, the physical structure available for the factory, the engineering part of the project and the organic- functional structure which facilitates to determine the business group, the constituent parts, organization and operating manuals for the proper operation of the company. 5 Within the economic- financial study the total project investment was determined which is 28,955.80 $, and the 58.56% will be financed by the members of the company and 41.44% by the Banco National de Fomento. Finally, according to the research results of the feasibility of the project was determined for which the following indicators were analyzed: the current net value of $ 31,935.44; the Internal Rate of Return of 55.48%; the cost-benefit relationship is about $ 1.25 for every dollar invested the company earns 0.25 cents; the Capital Investment Recovery Period is 1 year, 8 months and 1 day; the Sensitivity analysis indicates that the project supports an increase in costs of 11.80% giving a total of 0.99% and the sensitivity analysis in the decrease in the income of 9.43% giving a total of 0.99%, thus the project is feasible, thus the conclusions and recommendations determined this, attached by the bibliography consulted with their respective annexes.